2022
DOI: 10.1002/alz.067434
|View full text |Cite
|
Sign up to set email alerts
|

APOE e4 dependent deficits in brain DHA phospholipids and mfsd2a in Alzheimer’s disease patients with severe cerebral amyloid angiopathy

Abstract: BackgroundThe apolipoprotein E e4 allele (APOE4) is a major risk factor, contributing to vascular pathologies in AD which include CAA, BBB dysfunction and reduced cerebral vascular integrity. The diminished capacity of APOE4 to transport docosahexaenoic acid (DHA), an essential fatty acid required for the structural and functional maintenance and vascular integrity of the brain, could also contribute to AD pathogenesis. However, it remains undetermined if changes in the brain DHA content of phospholipids (PL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other studies on E4FAD mice and humans showed a lower MFD2a expression in brain homogenates of those carrying the ApoEε4 allele compared to that in ApoEε3 carriers. The ApoEε4 genotype was associated with reduced MFSD2a expression and DHA levels [116]. A lower expression of MFSD2a will decrease DHA levels in the brain, resulting in neuronal death, cognitive dysfunctions, and microcephaly [114,117].…”
Section: Mfsd2a Symportermentioning
confidence: 97%
“…Other studies on E4FAD mice and humans showed a lower MFD2a expression in brain homogenates of those carrying the ApoEε4 allele compared to that in ApoEε3 carriers. The ApoEε4 genotype was associated with reduced MFSD2a expression and DHA levels [116]. A lower expression of MFSD2a will decrease DHA levels in the brain, resulting in neuronal death, cognitive dysfunctions, and microcephaly [114,117].…”
Section: Mfsd2a Symportermentioning
confidence: 97%